2017
DOI: 10.1108/jeim-01-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Burnout during early career: lived experiences of the knowledge workers in India

Abstract: Purpose The purpose of this paper is to explore the phenomenon of burnout during early career among knowledge workers in information technology (IT) services industry in India. Design/methodology/approach The grounded theory research design was used to explore the research phenomenon. The study was based on the analysis of 43 in-depth interviews from the employees, managers and human resource professionals in IT services industry in India. Purposeful and theoretical sampling designs were used to locate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
5
0
1
Order By: Relevance
“…Also, workplace burnout results in productivity loss and employee turnover (Ahola et al, 2006). According to Packirisamy et al (2017), burnout has an impact on the human system and thereby influences productivity and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, workplace burnout results in productivity loss and employee turnover (Ahola et al, 2006). According to Packirisamy et al (2017), burnout has an impact on the human system and thereby influences productivity and performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, an open-ended paradigm is proposed to bridge the gaps between the research and design practice of restorative green spaces. 信息时代,知识正在改变全球经济与劳动力市场 [1] 。知识工作者已 成为世界各国生产力与竞争力的基本驱动因素 [2][3] 。通过开发用于电子 商务、人工智能、自动化技术与线上交流合作的数字工具,知识工作者 在地缘政治较量、文化与社会冲突、人口老龄化,以及当前新冠肺炎 (COVID-19)疫情等问题上发挥了关键作用 [4] 。 然而,越来越多的证据表明,许多知识工作者因为知识型工作的固 有特性 [5] --包括久坐的工作状态、长期高强度脑力劳动与高度职业竞 争 [6]~ [8] --正遭受着生理和心理健康问题的困扰(表1)。世界卫生组织 表示,健康问题造成全球生产力下降,由此导致的经济损失每年约1万亿 美元 [9] 。本研究总结了在知识型工作者中普遍存在的四类健康问题:心理 压力、心理疲劳、缺乏体力活动,以及社会孤立/冲突 [6][10] 。 1)久坐的工作状态:知识型工作通常在计算机上操作,因此,知识 工作者的大部分工作时间都是坐在电脑屏幕前度过的。这种久坐的工作 状态可能导致静态/缺乏活动的生活方式,造成心理压力、精神疲劳和 社会孤立,进而损害知识工作者的心理健康 [11]~ [13] 。此外,久坐的工作状 态还限制了知识工作者体力活动的时间和意愿,增加其患肥胖症、心血 管疾病、II型糖尿病、癌症和其他严重生理疾病的风险 [14][15] 。 2)长期高强度脑力劳动:知识型工作通常需要长时间地保持专注, 这会快速耗费工作者的注意力,导致精神疲劳 [16][17] 。各种期限紧迫的任 务可能进一步导致严重的心理压力与焦虑 [18][19] 。长期高强度脑力劳动也 会给知识工作者带来负面情绪,以及难以控制的冲动和攻击性行为,这 增加了社会冲突的隐患 [20][21] 。此外,这种繁重工作可能极大压缩知识工 作者进行休闲体力活动的时间和精力 [14] 。…”
Section: Discussionunclassified
“…However, a growing body of evidence shows that many knowledge workers are suffering from physical and mental health problems caused by the inherent characteristics of knowledgebased occupations [5] , such as sedentary work, long-time and intense mental labor, and high-level occupational competition [6]~ [8] (Table 1). According to the World Health Organization (WHO), the global decline in productivity caused by health problems results in annual losses of more than one trillion USD [9] .…”
Section: Introduction: Health Crisis Of Knowledge Workers 1health Pro...mentioning
confidence: 99%
“…Most of the preceding research have absorbed the dynamics of ER of Indian firms in the manufacturing sector. Nevertheless, a few studies have indicated the vulnerability of the working class in the IT sector (Bandla, 2019; Firdausi, 2020; Packirisamy et al, 2017; Rathore & Ahuja, 2015). The studies that portrayed the ER have focused on the issues of the ITES sector, which are quite different due to the varying nature of work, skills and quality of work and the working conditions.…”
Section: Literature Review-mentioning
confidence: 99%